Life Skill Dan Keharusan Penataan Kembali Pendidikan Indonesia - Toharuddin, Toharuddin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2003)
General Life Skill is a set of skills which is needed by those who are either already working or still studying. General Life Skill (GLS) comprises personal skill which consists of self-awareness and rational thinking and social skills. In Life Skill concept, this general life skill is prioritized to be developed. The problem is, in the practice of education, it is often